Inclusive growth in the Peoples Republic of China a deep look at men and womens work amid demographic, technological, and structural transformations. - Dong, Xiao-Yuan (East Asia working papers., 2019)
Three types of gender based constraints that hamper inclusive growth are identified: gender gaps in educational attainment; gender stereotypes affecting employment decisions; and competing demands of work and family, especially on women. The paper recommends (i) investing in rural women with a targeted approach, (ii) developing elderly care services, (iii) tackling gender stereotyping and segregation in occupations, (iv) increasing public spending on early childhood education and care, and (v) considering pension reform.